Oil-growth nexus in oil producing countries: macro panel evidence - Fuinhas, José Alberto (2019)
The oil consumption-economic growth nexus is examined in a panel of oil producing countries over a long time span (1965-2012). Both, the ratio of oil production to primary energy consumption, i.e. oil self-sufficiency, and the persistence of the second structural oil shock were controlled for. The phenomenon of cross-sectional dependence that is present in the panel confirms that these countries share common spatial patterns, unobserved common factors, or both. The cointegration/long memory relationships as well as the panel data estimators’ appropriateness are analysed and discussed. A dynamic Driscoll-Kraay estimator, with fixed effects, was shown to be adequate to cope with the phenomena of heteroskedasticity, contemporaneous correlation, first order autocorrelation and cross-sectional dependence present in the panel. The results are consistent with the growth hypothesis, i.e. that oil consumption proves be a driver of economic growth. The second structural oil break (1979), reveals the long-lasting positive effect exerted by oil consumption on growth. The ratio of oil production to primary energy consumption has exerted a positive impact on growth. Thus, policymakers should take into account the benefits of promoting oil self-sufficiency, by reinforcing the use of endogenous resources